Aquasomes; A New Approach for Delivering Therapeutics: An Overview - Chaudhary, Jitendra Singh (Asian Journal of Pharmaceutics (AJP), 2018)
Novel drug delivery systems such a ethosomes, niosomes, polymeric liposomes, proliposomes, aquasomes, nanoparticles, nanocapsules, nanoemulsions, and microspheres offer a great advantage over conventional drug delivery systems in terms of drug safety, bioavailability, stability, improved tissue macrophage distribution, and sustained and controlled drug release. Aquasomes can be considered to the most recently developed drug delivery system for therapeutics as they possess the ability to deliver active molecules such as proteins, peptides, hormones, antigens, genes, and drugs of diverse categories to specific sites. Aquasomes are round nanoparticulate drug delivery systems of around 60–300 nm in size with three-layered self-assembled structures (by ionic or non-covalent bonding) comprising of a central solid nanocrystalline core coated with polyhydroxy oligomeric film onto which biochemically active molecules are adsorbed with or without modification. Solid core renders stability against dehydration and provides stabilization to the biochemically active molecules. Three types of core materials are primarily used for fabricating aquasomes: tin oxide, nanocrystalline carbon ceramics (diamonds), and brushite (calcium phosphate dihydrate). Calcium phosphate is the core of interest, owing to its natural presence in the body. This review provides an overview about aquasomes and it provides protection and preservation of fragile biological molecules, conformational integrity, and surface modification makes them attractive carrier system to delivery of drugs, especially through transdermal route.